Factors that Influence Coffee Payment Rates of Coffee Societies in Imenti North and Buuri Districts of Meru County,Kenya - Kaburu,Eliezer (Meru: Eliezer Kaburu, 2014)
The importance of coffee to the world economy cannot be overstated.it is one of the most valuable primary products in world trade,in many years second in value only to oil as a source of foreign exchange to producing countries.That is why this study was carried out to analyse factors that influence payment rates of coffee societies in Imenti North and Buuri Districts of Meru County,Kenya.Descriptive research design was used in this study.the target population was 56 top leadersof seven coffee cooperative societies in Imenti North and Buuri Districts.Census was carried out in this study.Data was collected by use of questionnaires whereby reliability and validity of questionnaires were assessed through pilot testing.Data was analysed through quantitative and quasi-statistics analysis methods and presented in tables and pie charts.It was found that coffee societies in he two societies produced all known grades of coffee.They produced high quantities of grade C and AB which are of lower rank than grade AA.It was found that in Imenti North district administration and milling costs were major expendituresand took a major substantial proportion of sales revenue.In Buuri district the major expenditures were on factory processes and administration.It was found that all the societies had five year strategic plans.Training of management committees was good.However employees and farmers' training were not good.It was found that practices related to farmers capacity building were not taken with the weight they deserved.The results indicated that all the factors had influence on payment rates of coffee societies in the two districts.From the study,it was recommended that strict controls be applied on all expenditures and management committees to be more forcused on training farmers on coffee husbandry in order to get better grades.It was recommended that further study be conducted to establish farm level activities practiced by farmers and how to improve coffee cash flows through value addition and expansion market by getting local market to avoid over depending on foreign markets.
Includes Appendix and Reference